The Influence of Income Level, Financial Behavior and Financial Management on Financial Well-Being in the Sandwich generation: Study in Sukaragam Village, Serang Baru District - Anjani, Dinda Dewi; Siska Wulandari (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research is intended to assess the influence of income level, financial behavior and financial management on financial well-being. This research is quantitative in nature and involves a population that includes various variables, such as age, gender, occupation, and level of income/pocket money (monthly) in Sukaragam village. The sampling method in this research used non-probability sampling. Data was obtained from a number of respondents through questionnaire distribution, both conventionally and via online Google Form. Data analysis was carried out using SPSS version 26 software by applying the multiple linear regression method. Descriptive statistical approaches, instrument testing, classical assumption testing, and hypothesis testing were also used in the data analysis process for this research. The research results show that income level and financial management do not have a significant influence on financial well-being. On the other hand, financial behavior has been proven to have a significant positive influence on financial well-being